Nonlinear fiber lasers using Bismuth based Erbium doper fiber amplifier / Sharifeh Shahi - Shahi, Sharifeh (2010)
A thorough study on Bismuth-based Erbium-doped fiber (Bi-EDF) is presented for wide-band amplifiers and multi-wavelength fiber laser applications. This fiber allows high Erbium ions concentration to be doped without a significant concentration quenching effect. The high refractive index characteristic in the Bi-EDF has broadened the emission spectrum of Erbium ions to achieve a broader gain spectrum up to extended L-band region compared to normal silica-based Erbium-doped fiber (EDF). The Bi-EDFA performances have been investigated in terms of power conversion efficiency (PCE), quantum conversion efficiency (QCE), gain and noise figure. The highest QCE and PCE for a 215 cm long of Bi-EDF are estimated to be approximately 23.7% and 25.7%, which is obtained at 1605 nm. With bi-directional pumping, the maximum gain of 34 dB is obtained at approximately 1570 nm. The operation of the bi-directional Bi-EDFA covers from C-band to the extended L-band regions. Furthermore, various configurations on the multi-wavelength fiber lasers have been proposed and demonstrated using the Bi-EDF as both the linear and nonlinear effects. Nonlinear effects such as the stimulated Brillouin scattering (SBS) and four-wave mixing (FWM) are used in the fiber lasers to generate multi-wavelength comb lines. The Brillouin Erbium fiber laser (BEFL) is able to produce a stable comb with 50 lines at extended L-band region using only a Bi-EDF as the gain medium. The multi-wavelength fiber laser has also been demonstrated for the first time based on a Bi-EDF assisted by a FWM process. The estimation of the nonlinear parameters of Bi-EDF was also proposed based on the FWM effect. With a simple ring cavity, the laser generates more than 10 lines of optical comb with a line spacing of approximately 0.41nm at 1615.5 nm region using 146 mW of 1480 nm pump power.